ANALISIS CASE MIX INDEX PELAYANAN RAWAT INAP RUMAH SAKIT YANG BEKERJA SAMA DENGAN BPJS KESEHATAN TAHUN 2019-2020 - Ambarita, Anna Tirawani; Nurwahyuni, Atik (UI Scholars Hub, 2023)
BPJS Health experienced various challenges in achieving Universal Health Coverage / Jaminan Kesehatan Nasional (JKN), including a referral system. According to the 2018 National Health Account, curative spending costs reached 69.1%. The Case Mix Index (CMI) is a benchmark for hospital performance abroad, but Indonesian hospitals have not used it. In 2019, BPJS Health tested CMI in 30 hospitals. The research uses sample data from 2019-2020 based on province, hospital type and ownership. The methods used are anova test, independent T, linear regression and multiple linear regression. The research results show a decrease in cases in 2019-2020. The highest CMI was in region 1, hospital A, and the private sector. The beta coefficient value for the proportion of male gender, elderly age, PBI APBD participants, and class 1 is greater than for CMI. CMI inpatients in 2019 is related to region, type of hospital, hospital ownership, proportion of children, proportion of productive, proportion of elderly, proportion of BP, proportion of PBI APBN, proportion of PBI APBD, proportion of PBPU, and proportion of class 1. CMI of inpatients in 2020 related to region, type of hospital, hospital ownership, proportion of men, proportion of women, proportion of children, proportion of productive, proportion of elderly, proportion of BP, proportion of PBI APBN, proportion of class 1, and proportion of class 3. It is hoped that the government will accelerate the distribution of services health and BPJS Health monitor hospital CMI.